A CHARACTERIZATION TECHNIQUE FOR THE DEGRADATION CHARACTERISTICS OF TI/SI SCHOTTKY-BARRIER DIODES AND OHMIC CONTACTS AFTER THERMAL SILICIDATION - LOU, YS; WU, CY (My University, 1994)
The effects of thermal silicidation on both the nonideal current-voltage characteristics of the Schottky-banier diodes and the degradation properties of the ohmic contacts have been self-consistently characterized by using a simple interfacial-layer theory. The abruptly changed nonideality of the measured I-V characteristics as TiSi2 is formed can be interpreted as the variations of the interface properties, such as the thermal-equlibrium barrier height, the interfacial-layer capacitance, and the density distribution of the interface state. Moreover, different work functions for Ti and TiSi2 and the change of the dominant type of the interface states and their density distributions are shown to be responsible for the fluctuations of the thermal-equilibrium barrier height after thermal silicidation. Furthermore, the interface parameters extracted from the fabricated Schottky-barrier diodes are used to calculate and compare the simultaneously-processed specific contact resistivities, and satisfactory agreement is obtained. Thus, the silicidation-related degradation characteristics of the ohmic contacts can be directly related to the variations of the interface properties at the Ti/Si interface.